Central nervous system tuberculosis presenting as epilepsia partialis continua: A case report - Berilgen, M. S.; Kalkan, A.; Demirdag, K.; Bulut, S.; Ozden, M.; Mungen, B. (Blackwell Publishing, 2004)
[Abstract Not Available]